A review of Drilini (Coleoptera: Elateridae: Agrypninae) of the Northern Levant, with description of a new species from Syria and a key to Levantine species - Kundrata, Robin; Kobieluszova, Lucie; Bocak, Ladislav (Zootaxa, 2014)
The species of the elaterid soft-bodied tribe Drilini from the Levant are reviewed. All known species are redescribed and Drilus nemethi sp. nov. is described. Drilus adustus (Chevrolat, 1854), comb. nov. and D. akbesianus (Fairmaire, 1895), comb. nov. are transferred from Malacogaster Bassi, 1834 to Drilus Olivier, 1790. Drilus posticus Schaufuss, 1867, syn. nov. is a junior subjective synonym of Drilus adustus (Chevrolat, 1854). All Levantine species are keyed and diagnostic characters are illustrated. Their distribution, morphological diversity and the statuses of type specimens of Drilus reitteri Bourgeois, 1908 and Cydistus reitteri Bourgeois, 1885 are discussed.
Keywords: demografie; brouci; mužské pohlaví; druhová specificita; zvířata; Coleoptera; Demography; Syria; Sýrie; Male; Species Specificity; Animals